IMPLEMENTASI KEBIJAKAN LAYANAN INSAN UTAMA DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PAYAKUMBUH - Usfa Haryanti; Tun Huseno (Journal Publicuho, 2024)
The purpose of this study is to analyze the process and results of INSAN UTAMA service policy implementation in Payakumbuh City, West Sumatra. Qualitative methods were used to identify the drivers of INSAN UTAMA service policy implementation from the perspectives of policymakers and service users in Payakumbuh City. Data collection was conducted through semi-structured interviews. Data analysis was conducted using triangulation techniques, namely data reduction, data presentation, and conclusion drawing. The results found that the process of implementing the INSAN UTAMA service policy was carried out by the INSAN UTAMA service coordination team, namely the Population and Civil Registration Office (Disdukcapil) and the Ministry of Religion (Kemenag), with the Religious Affairs Office (KUA) as the technical implementer. INSAN UTAMA service users obtained accelerated issuance of identity cards, such as identity cards (KTP) and family cards (KK), shortly after the marriage contract was held. Service users were satisfied with the performance of the INSAN UTAMA service. The INSAN UTAMA service can be a model for Disdukcapil in other districts or cities. The research implications emphasize the importance of communication in the substance of a policy. Through communication, it will be easier to mobilize both human resources, information, authority, and necessary facilities. Bureaucratic structure and disposition also play an important role in determining the success of implementing a policy.